Multicentre survey to explore current survival of patients with acute myeloid leukaemia who failed induction chemotherapy. (17th August 2015) - Lazzarotto, Davide; Candoni, Anna; Nadali, Gianpaolo; Pavan, Laura; Lessi, Federica; Mosna, Federico; Simeone, Erica; Ventura, Giovanna; Gherlinzoni, Filippo; Semenzato, Gianpietro; Pizzolo, Giovanni; Fanin, Renato
Abstract: Background: Acute myeloid leukaemia not responsive to first induction chemotherapy (PIF‐AML) still remains a challenge, and there are only few recent epidemiological data regarding the outcome of these patients. In this multicentre survey, we evaluate the prognosis and outcome of patients with PIF‐AML, who were diagnosed and treated in the last 5 yrs in four Italian institutions. Results: One hundred PIF‐AML were recorded, 57 males and 43 females, with a median age of 63 yrs (19–79), 42% were younger than 60 yrs; 42% had a secondary AML and 40% had an adverse karyotype. According to cytogenetic/molecular risk stratification at diagnosis, 33% of patients were classified as favourable/intermediate‐1 risk and 56% as intermediate‐2/adverse risk. After a median follow‐up of 11 months (1–49), 77% of patients died, while 23% were alive (with 12/23 in cCR). Thirty‐six patients underwent allogeneic SCT, and of these, 11 of 36 (31%) were alive at last follow‐up. The 12‐ and 24‐month OS probability of the whole population was 45% and 21%, respectively. In multivariate analysis, the probability of OS of the whole population was significantly improved by Allo‐SCT procedure (12‐month OS probability 60% vs. 35%; P < 0.0001) and was better in patients with favourable/intermediate‐1 risk at diagnosis (12‐month OS probability 58% vs. 40%; P = 0.028). In transplanted cases, a pretransplant responsive disease was the only significant factor to predict a favourable outcome after Allo‐SCT ( P = 0.006). Conclusion: Treatment options of PIF‐AML still are limited and the prognosis, even recently, remains extremely poor. This survey shows that PIF‐AML is still rarely cured without Allo‐SCT and confirms the importance of initiating an urgent unrelated donor search in cases without a matched sibling donor. Moreover, the outcome of Allo‐SCT is better in patients who achieve a good AML debulking before transplant. To reach this goal, new predictive scores and new protocols of salvage therapy (with target drugs or combinations) need to be explored urgently in PIF‐AML.